2008
DOI: 10.1074/jbc.m800956200
|View full text |Cite
|
Sign up to set email alerts
|

An Oncogenic Role for the Phosphorylated h-Subunit of Human Translation Initiation Factor eIF3

Abstract: Dysregulation of protein synthesis has been implicated in oncogenesis through a mechanism whereby "weak" mRNAs encoding proteins involved in cell proliferation are strongly translated when the protein synthesis apparatus is activated. Previous work has determined that many cancer cells contain high levels of eIF3h, a protein subunit of translation initiation factor eIF3, and overexpression of eIF3h malignantly transforms immortal NIH-3T3 cells. This is a general feature of eIF3h, as high levels also affect tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 36 publications
6
64
0
Order By: Relevance
“…Further evidence implicating eIF3h levels in cancer comes from experiments that reduce the level of eIF3h in a prostate cell line that exhibits high eIF3h levels. Down-regulation of eIF3h causes the cells to lose their ability for anchorage-independent growth and to become more susceptible to apoptosis (57). The results indicate that elevated levels of eIF3h are required to maintain the cancerous state of these prostate-derived cells.…”
Section: Regulation Of Eif3 Is Important In Controlling Cell Prolifermentioning
confidence: 79%
See 1 more Smart Citation
“…Further evidence implicating eIF3h levels in cancer comes from experiments that reduce the level of eIF3h in a prostate cell line that exhibits high eIF3h levels. Down-regulation of eIF3h causes the cells to lose their ability for anchorage-independent growth and to become more susceptible to apoptosis (57). The results indicate that elevated levels of eIF3h are required to maintain the cancerous state of these prostate-derived cells.…”
Section: Regulation Of Eif3 Is Important In Controlling Cell Prolifermentioning
confidence: 79%
“…Nor is it clear how overexpression of the 3h or 3i subunit, which does not alter the level of eIF3, stimulates protein synthesis and cell proliferation. Further experiments with a stable cell line where eIF3h synthesis can be induced show that the malignant phenotypes emerge within about 8 h of induction, just as the level of eIF3h and the tightly coupled rate of protein synthesis increase, suggesting that protein synthesis is directly involved (57). However, no malignant transformation occurred with induced overexpression of a mutant form of eIF3h, where Ser-183 is changed to alanine to prevent phosphorylation at that site, indicating that phosphorylation of eIF3h is required for induction of malignancy.…”
Section: Regulation Of Eif3 Is Important In Controlling Cell Prolifermentioning
confidence: 99%
“…18 Two eIF3 core subunits, eIF3A and eIF3H, were chosen, both of which are suggested to be involved in translation of certain mRNAs. 58,59,63,99 Furthermore, eIF3A, the largest and conserved eIF3 subunit, may control the assembly and stability of eIF3 as well as the formation of different sub-complexes with additional functions within the mammalian cells. 64,100 However, differently from the Drosophila homolog, ABCE1 silencing in our system did not reduce the levels of eIF3A and eIF3H (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the human ortholog of eIF3h is highly expressed in many cancer cells, and its high levels trigger dysregulation of protein synthesis. This oncogenic potential of eIF3h is strongly enhanced by phosphorylation at the conserved residue Ser-183 (Zhang et al, 2008). Recent research revealed that translation regulation via uORFs contributes to plant development, playing important roles in organogenesis.…”
Section: Role Of Tor In Regulation Of Translation Of Specific Mrnas Mmentioning
confidence: 99%